A preterm lifeline: Early discharge programme based on family‐centred care. Issue 4 (20th July 2015) - Brødsgaard, Anne; Zimmermann, Renathe; Petersen, Mette
Abstract Purpose To present an Early Discharge Programme model for preterm infants based on family‐centred care, and to describe its impact on the infants and families. Design and Methods Methods included longitudinal growth assessments of 218 premature infants and a qualitative synthesis of two focus group interviews with 15 parents. Results The main finding was the experience of "parents in control with lifeline to neonatal intensive care unit" based on five syntheses. Practice Implications An early discharge programme based on family‐centred care has been implemented and integrated into our neonatal intensive care unit that could be implemented by other hospitals.